Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing pada Pempek Feri Palembang - Siska Amalda; Bakti Setyadi; Dewi Sartika; M. Titan Terzaghi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the calculation of the cost of production at UMKM Pempek Feri Palembang using the full costing method. The research method applied is descriptive qualitative with a case study approach. Data were collected through observation, documentation, and interviews to obtain information regarding raw material costs, direct labor, and factory overhead costs. The results indicate a difference between the company’s calculation of the cost of production and the full costing method, where the full costing method provides more accurate results as it includes all cost components, both variable and fixed. Therefore, the implementation of the full costing method can assist the company in determining a more precise selling price and improving the accuracy of production cost control.